Exploring the roles of Mus81-Eme1/Mms4 at perturbed replication forks. - Osman, F; Whitby, M (2007)
Cells of all living organisms have evolved complex mechanisms that serve to stabilise, repair and restart stalled, blocked and broken replication forks. The heterodimeric Mus81-Eme1/Mms4 structure-specific endonuclease appears to play an important role(s) in homologous recombination-mediated processing of such perturbed forks. This enzyme has been implicated in the cleavage of stalled and blocked replication forks to initiate recombination, as well as in the processing of recombination intermediates that result from repairing damaged forks. In this review we assess the biochemical and genetic evidence for the mitotic role of Mus81-Eme1/Mms4 at replication forks and in repairing post-replication DNA damage. Mus81 appears to act when replication is impeded by genotoxins or by impairment of the replication machinery, or when arrested replication forks are not adequately protected. We discuss how its action is regulated by the S-phase cell cycle checkpoint, depending on the nature of the stalled or damaged fork. We also present a new way in which Mus81 may limit crossing over during the repair of post-replication gaps, and explore Mus81's interplay with other components of the recombination machinery, including the RecQ helicases that also play important roles in processing replication and recombination intermediates.